A Novel Strategy for the Mechanical Subpulmonary Support in Failing Fontan Patients - Dal Sasso, Eleonora; Schöndorf, Thomas; Schlüter, Kim-John; Miera, Oliver; De Rita, Fabrizio; Menon, Ares K.; on behalf of the European EXCOR® Pediatric Investigator Group (EEPIG) (The Thoracic and Cardiovascular Surgeon, 2022)
Background The number of single ventricle patients undergoing Fontan palliation and surviving to adulthood worldwide has steadily increased in recent years. Nevertheless, the Fontan circulation is destined to fail. Ultimately, heart transplantation (HTx) remains the definitive treatment option. Due a shortage of organs, mechanical circulatory support in the form of ventricular assist devices (VADs) is widely used to bridge heart failure patients to HTx, but these devices have been mainly developed to address the needs of normal anatomies. A novel venous cannula has been developed as part of the EXCOR® VAD to provide subpulmonary support in these patients. Its clinical application is investigated in the “Registry to Assess the Safety and Feasibility of the Subpulmonary Support with the Novel Venous Cannula in Patients with Failing/Absence of the Right Heart” (RegiVe study, NCT04782232).Methods RegiVe is a multicenter, international, observational, prospective, non-randomized registry aiming to collect the routine clinical data of up to 20 patients. The primary endpoints address device performance and safety, while the secondary endpoints target organ status and overall safety (according to the Interagency Registry for Mechanically Assisted Circulatory Support – INTERMACS – definitions). Data analysis will be performed by means of descriptive statistics.Results RegiVe has received the favorable opinion of an independent ethics committee and enrollment has recently started.Conclusion RegiVe is the first study evaluating the use of a medical device specifically developed for subpulmonary support of failing Fontan patients. The study will provide important insight and further information on this cohort and help to improve a dedicated VAD strategy.
Keywords: circulatory assist devices; congenital heart disease; transplantation; heart